1994
DOI: 10.1523/jneurosci.14-11-06354.1994
|View full text |Cite
|
Sign up to set email alerts
|

Calcium imaging of rhythmic network activity in the developing spinal cord of the chick embryo

Abstract: Video-rate imaging of spinal neurons loaded with calcium-sensitive dyes was used to investigate the calcium dynamics and cellular organization of spontaneously active rhythm-generating networks in the spinal cord of E9-E12 chick embryos. Spinal neurons were loaded with bath-applied fura-2am. Motoneurons were also loaded by retrograde labeling with dextran-conjugated, calcium-sensitive dyes. Dye-filled motoneurons exhibited large fluorescent changes during antidromic stimulation of motor nerves, and an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 24 publications
7
93
0
Order By: Relevance
“…The first was the pathway from the V L F onto both motoneurons and interneurons. This was selected because previous work had shown that some of the interneurons projecting into the V L F were active during spontaneous episodes (O'Donovan et al, 1994, O'Donovan andRitter, Wenner, Ho, Whelan, and O'Donovan, unpublished data). The second pathway was the disynaptic, recurrent connection between motoneurons, which may be equivalent to the mammalian Renshaw pathway (Whelan and O'Donovan, 1997;Wenner et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…The first was the pathway from the V L F onto both motoneurons and interneurons. This was selected because previous work had shown that some of the interneurons projecting into the V L F were active during spontaneous episodes (O'Donovan et al, 1994, O'Donovan andRitter, Wenner, Ho, Whelan, and O'Donovan, unpublished data). The second pathway was the disynaptic, recurrent connection between motoneurons, which may be equivalent to the mammalian Renshaw pathway (Whelan and O'Donovan, 1997;Wenner et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…A similar approach involving retrograde labeling of neurons, which we call "functional neural tracing," was used here to label XII preMNs and MNs. Our population labeling approach, based on axonal projections and network connectivity, and using acetoxymethyl (AM) forms of Ca 2ϩ -sensitive dyes, is an extension of the methods originally described by O'Donovan et al (1994) and Fetcho and O'Malley (1995) for retrograde labeling of neurons in brainstem-spinal cord motor circuits with Ca 2ϩ -sensitive dyes. Our use of a membranepermeant AM ester form of dye enabled us to retrogradely label neurons with Ca 2ϩ -sensitive dye through axons of passage without affecting axonal or network function (Koshiya and Smith, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…In humans, the presence of these patterns is clinically relevant as their absence is thought to reflect a bad prognosis (510). In a series of investigations, O'Donovan and collaborators (190,478,480) reported that the embryonic chick spinal cord has spontaneous activity generated by somewhat hyperexcitable networks that can be recorded already in ovo. They exhibit rhythmic discharge both with slow episodes (lasting minutes) and fast intraepisode cycling (ϳ1 Hz frequency).…”
Section: The Spinal Cordmentioning
confidence: 99%